Analysis Of Symbols, Declarations and Punctuations Through Conversion of C Language Into English Language With Borland C++ - Mac Aditiawarman; Rera Abel Gemilang (Fakultas Sastra Universitas Ekasakti, 2020)
This research with the title The analysis of symbols, punctuations and declarations in C language is analyzed accordingly by conversion in order to find the perspective of language: structuralism, meaning, and functionalism, while keeping both of English and computer subject in process for the research. This research has limitation by the chosen of platform and software with Borland C++, the source of the datum also considered to be the basic material so that this thesis doesn’t has many problems to solve.By the observation method which is followed by these three crucial problems: (1) The Identification of semiotic problem in symbols from computer language to English language, (2) The Identification of semiotic problem in declarations from computer language to English language, (3) The Identification of semiotic problem in declarations from computer language to English language. The implication of the problem here is how the researcher convert the C language into English language patterns.The purpose of this research is equally to identify and analyze the symbols, punctuations and declarations from the Borland C++ platform and converting it into English comprehensions. Furthermore, this research is expected to familiarize the reader with which semiotics usually use in C or programming language and what’s their significant in English language.In this research, the researcher utilizes semiotics theory and computer programming theory which these two subjects combined together and creating the subject of interdisciplinary called Computational Semiotic.